Laboratory Configurations for PCM-TES Materials: A Review - Munteanu , Ioana G.; Tudose, Eugenia T. Iacob (Journal of Advanced Thermal Science Research, 2022)
The global energy crisis and the negative impact on the environment of the existing technologies have constrained researchers to capture several types of waste energy using different technologies and materials. For heat, energy harvesting technologies include a major source, the sun, and as an effective storage media, phase change materials. The current review covers experimental laboratory configurations used for thermal energy storage (TES), mainly with phase change materials as working fluids. The required characteristics of PCM-TES materials are covered. Geometric configurations, starting with simple shell-and-tube heat exchanger (HX), other multiple constructive alternatives, plate HX, and also modular HX or fixed and fluidized beds systems are overviewed in order to concentrate on heat transfer characteristics important for TES systems operation and optimization. Emphasis falls on important constructive characteristics for thermal performance, such as the heat charge and discharge rates, within specific temperature ranges, depending on the type of TES fluid used, the energy storage capacity, or density. The advantages and disadvantages of each constructive piece of equipment are critically reviewed. Some comparisons among designs are also included, with an accent on beneficial alterations to improve thermal features.